2021
DOI: 10.1109/jstars.2021.3089851
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Patterns of Land Surface Temperature Change in the Tibetan Plateau Based on MODIS/Terra Daily Product From 2000 to 2018

Abstract: Under the background of climate change, the Tibetan Plateau presents high spatial and temporal variability in land surface temperature (LST). To understand the spatiotemporal patterns of LST change, this study conducted a spatiotemporal analysis using the Mann-Kendall trend analysis method with time series of mean annual surface temperature (MAST) extracted from the MODIS/Terra daily LST product from 2000 to 2018. The analysis indicated that both daytime and nighttime MASTs show an obvious warming trend with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 87 publications
(104 reference statements)
3
19
0
Order By: Relevance
“…In recent years, there have been studies using MODIS data to analyze the temporal and spatial patterns of regional surface temperature, and good results have been achieved [64]. However, local meteorological conditions, such as clouds, have a great impact on satellitederived LST, resulting in many missing values, which makes it difficult to obtain continuous LST changes in space and time.…”
Section: Lst Reconstruction Methodsmentioning
confidence: 99%
“…In recent years, there have been studies using MODIS data to analyze the temporal and spatial patterns of regional surface temperature, and good results have been achieved [64]. However, local meteorological conditions, such as clouds, have a great impact on satellitederived LST, resulting in many missing values, which makes it difficult to obtain continuous LST changes in space and time.…”
Section: Lst Reconstruction Methodsmentioning
confidence: 99%
“…Similarly, a monthly analysis of temperature data for the years 2000, 2010, 2015) has also been carried out to assess the temperature dynamics. It is observed that after 2000, there is a slight increase in the monthly maximum and average temperature over the years and no significant changes in monthly minimum temperature.…”
Section: Trends In Temperaturementioning
confidence: 99%
“…Therefore, the land-use dynamics especially the increase of the built-up area makes a notable change in LST (Akter et al, 2021;Gazi et al, 2021), as it is strongly influenced by emissivity properties of different LULC classes (Cheng and Liang, 2018). The LST study has great potential for insolation, heat budget, and overall climate change studies (Halder et al, 2021;Salwan et al, 2021;Yang et al, 2021). This climate change has strong contributions to human life and biophysical parameters (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The vehicle’s GPS (Global Positioning System) can not only locate and detect the longitude and latitude coordinates of the vehicle, but can also detect the real-time elevation of the road surface [ 19 ]. However, conventional GPS can only detect statically or obtain the elevation data of the surface through calculation after the detection, which is relatively inefficient.…”
Section: Gps System For Road Undulation Elevation Detectionmentioning
confidence: 99%